Development as unfreedom : the role of mine migrant labour institutions as agents of development in the Transkei, 1886-1980s - Glover, Michael John (Department of Historical Studies, 2015)
Early liberal historians predominantly criticised the migrant labour system for its economic irrationality. After high GDP growth and steady benefits from gold mining in the 1960s, Marxist scholars in the 1970s pointed to the destructive impact of the system. Since 1994, the challenge inter alia has been to forge a new developmental path for the economy. In 2012 the National Development Plan set out its aim to “eliminate poverty and reduce inequality by 2030”.1 This is the challenge. For the country or region to ‘develop’ and eliminate ‘poverty’ we need to know what we are trying to eliminate and what our development is trying to achieve. This thesis examines the migrant labour system in the Transkei through a lens of development and asks how and to what extent the system inhibited the development of the Transkei and its peoples. Using Amartya Sen’s conception of development - which sees development as a process of expanding social, political, and economic freedoms/capabilities - this thesis offers a view of migrant labour institutions in terms of how they created and engendered deprivation and unfreedom in the Transkei. It is an attempt to understand our ‘developmental past’ and to understand how development in the Transkei has been frustrated and inhibited by formal institutions. Amartya Sen’s notions of ‘development’ and ‘deprivation’ offer an autonomy- and freedom-centred approach to thinking about poverty and development. Specifically the thesis examines the nexus of formal institutions underpinning the migrant labour system - including state laws, the Native Affairs Department, and the Native Recruiting Corporation - in terms of how they acted to inhibit the development of mineworkers and labour exporting regions like the Transkei.